Complement‐activated human endothelial cells stimulate increased polyfunctionality in alloreactive T cells. Issue 5 (1st February 2021) - Xie, Catherine B.; Zhou, Jing; Mackay, Sean; Pober, Jordan S.
Abstract : Antibody‐mediated deposition of complement membrane attack complexes (MACs) on IFN‐γ‐primed human endothelial cells (ECs) triggers autocrine/paracrine IL‐1β‐mediated EC activation and IL‐15 transpresentation to alloreactive effector memory T cells (TEM ), changes that enable ECs to increase T cell proliferation and cytokine release. Here, we report the use of single‐cell microchip 32‐plex proteomics to more deeply assess the functionality of the activated T cells and dependence upon EC‐derived signals. Compared to control ECs, MAC‐activated human ECs increase both the frequency and degree of polyfunctionality among both CD4 + and CD8 + ‐proliferated TEM, assessed as secreted proteins. IFN‐γ and TNF‐α remain the predominant cytokines made by alloreactive TEM, but a few CD4 + TEM also made IL‐4 while more CD8 + TEM made perforin and granzyme B. Increased polyfunctionality was attenuated by treatment of the MAC‐activated ECs with anti‐IL‐15 blocking antibody more effectively than IL‐1 receptor blockade. The increased polyfunctionality of T cells resulting from interactions with MAC‐activated ECs may further link binding of donor‐specific antibody to T cell–mediated allograft pathologies. Abstract : Analysis of the single cell protein secretome of human CD4+ and CD8+ effector memory T cells activated by coculture with allogeneic endothelial cells reveals that IL‐15, expressed on endothelium in response to alloantibody and complement‐mediated activation, increases both polyfunctionality and intensity of the T cell response, further linking humoral and cellular alloimmunity through endothelial cell interactions.